Do changes in torsional magnetic resonance imaging reflect improvement in gait after femoral derotation osteotomy in patients with cerebral palsy? - Braatz, Frank; Wolf, Sebastian Immanuel; Gerber, Annette; Klotz, Matthias C. M.; Dreher, Thomas (International orthopaedics, 2013)
Femoral derotation osteotomy (FDO) is commonly used to correct internal rotation gait (IRG) in spastic diplegia. The purpose of this study was to investigate whether the extent of intraoperative derotation is reflected in changes in static (clinical ROM and anteversion angle measured on torsional MRI) and dynamic parameters (transverse plane kinematics in three-dimensional gait analysis) after FDO in children with spastic diplegia.
Gesehen am 03.12.2020